Optic Nerve Tortuosity and Globe Proptosis in Normal and Glaucoma Subjects. Issue 8 (August 2019) - Wang, Xiaofei; Rumpel, Helmut; Baskaran, Mani; Tun, Tin A.; Strouthidis, Nicholas; Perera, Shamira A.; Nongpiur, Monisha E.; Lim, Winston E.H.; Aung, Tin; Milea, Dan; Girard, Michaël J.A.
Abstract : Précis: Eyes with glaucoma have tauter optic nerves compared with normal eyes, which may exert more force on the optic nerve head tissues during eye movements. Purpose: The purpose of this study was to assess the difference in optic nerve tortuosity during eye movements and globe proptosis between primary open angle glaucoma and normal subjects using orbital magnetic resonance imaging (MRI). Methods: Ten Chinese subjects matched for ethnicity and refractive errors were recruited, including 5 normal controls and 5 patients with primary open angle glaucoma. All subjects underwent MRI to assess their optic nerves and globes for 3 eye positions: primary gaze, adduction, and abduction. Optic nerve tortuosity (optic nerve length divided by the distance between 2 ends) and globe proptosis (maximum distance between the cornea and interzygomatic line) were measured from MRI images. Results: In adduction, the tortuosity of normal eyes was significantly larger than that of the glaucomatous eyes. Optic nerve tortuosity in adduction in the control and glaucoma groups were 1.004±0.003 (mean±SD) and 1.001±0.001, respectively ( P =0.037). Globe proptosis (primary gaze) in glaucoma subjects (19.14±2.11 mm) was significantly higher than that in control subjects (15.32±2.79 mm; P =0.046). Conclusions: In this sample, subjects with glaucoma exhibited tauter optic nerves and more protruding eye globes compared with normal eyes. This may impact optic nerve head deformations in anatomically predisposed patients. Abstract : Supplemental Digital Content is available in the text.